2019
DOI: 10.1007/s11661-019-05447-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Grain Refiner in the Nucleation of AlFeSi Intermetallic Phases During Solidification of a 6xxx Aluminum Alloy

Abstract: Primary grain refinement using inoculant additions and intermetallic compound (IMC) phase selection are critical aspects in the solidification of commercial aluminum alloys, controlling the final mechanical properties in service. Although there have been studies which suggest there are explicit interactions between the two phenomena, they have yet to be fully elucidated. Here, through study of intermetallic phase particles extracted from an inoculated casting, key features relating to the nucleation of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
2
15
1
Order By: Relevance
“…In AF-B, up to 45% of the primary IMCs were mobile regardless of thermal gradient or cooling rate, suggesting that they nucleated on TiB 2 particles. This provides evidence that TiB 2 can nucleate Fe-rich IMCs (at least as primary phase), as suggested by earlier researchers based on extraction and microscopy [29,44,45].…”
Section: Synchrotron X-ray Radiographysupporting
confidence: 84%
See 1 more Smart Citation
“…In AF-B, up to 45% of the primary IMCs were mobile regardless of thermal gradient or cooling rate, suggesting that they nucleated on TiB 2 particles. This provides evidence that TiB 2 can nucleate Fe-rich IMCs (at least as primary phase), as suggested by earlier researchers based on extraction and microscopy [29,44,45].…”
Section: Synchrotron X-ray Radiographysupporting
confidence: 84%
“…It was concluded that nucleation of platelet Fe-rich IMCs was not strongly influenced by the type of particle addition [18]. Extensive IMC extraction and microscopy by Lui et al [29] suggested that TiB 2 from the addition of commercial Al-5Ti-1B might be associated with nucleation of secondary Fe-rich IMCs, evidenced by observation of TiB 2 particles in physical contact with IMC platelets after extraction.…”
Section: Introductionmentioning
confidence: 99%
“…The free growth model [12] developed by Greer et al is commonly used to determine the potency of particles. [13][14][15] Zhang et al further considered the importance of crystallographic matching by applying their edge-to-edge matching model to explain the effectiveness of grain refiners and have successfully applied this to Al and Mg alloys. [6,[16][17][18] More recently, Fan et al [19] explained the growth of grains by elucidating the mechanisms of heterogeneous nucleation by epitaxial growth from substrates.…”
Section: Metal Fusion Additive Manufacturing (Am) Ismentioning
confidence: 99%
“…The segregation of Mg 2 Si and Al 5 Cu 2 Mg 8 Si 6 has been approved by some researchers [12][13][14] , but the formation of AlFeSi phase has aroused great controversy [15][16][17] . The types of the precipitation phase in 6061 alloy based on literature are shown in Table 3 [18][19][20] .…”
Section: Vol18 No1 January 2021mentioning
confidence: 99%